2016
DOI: 10.1016/j.zool.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Breeding biology of a winter-breeding procellariiform in the North Atlantic, the Macaronesian shearwater Puffinus lherminieri baroli

Abstract: Breeding biology of a winter-breeding procellariiform in the North Atlantic, the Macaronesian shearwater Puffinus lherminieri baroli.Zoology http://dx.doi.org/10. 1016/j.zool.2016.05.014 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…While the effect of rising SST on seabird reproduction has been well studied, less attention has been paid to the effect of air temperature (AT) on seabird reproduction (Fagundes, Ramos, Ramos, Medeiros, & Paiva, 2016;Sydeman et al, 2012) although terrestrial systems' response to such warming is well documented (e.g., Lebreton, 2011;Santisteban et al, 2012). Rising air temperatures impose direct thermal effects on marine vertebrates that breed on land and forage at sea (Croxall, Trathan, & Murphy, 2002).…”
mentioning
confidence: 99%
“…While the effect of rising SST on seabird reproduction has been well studied, less attention has been paid to the effect of air temperature (AT) on seabird reproduction (Fagundes, Ramos, Ramos, Medeiros, & Paiva, 2016;Sydeman et al, 2012) although terrestrial systems' response to such warming is well documented (e.g., Lebreton, 2011;Santisteban et al, 2012). Rising air temperatures impose direct thermal effects on marine vertebrates that breed on land and forage at sea (Croxall, Trathan, & Murphy, 2002).…”
mentioning
confidence: 99%
“…Research has shown that some seabirds show a preference for burrows that are orientated away from the prevailing wind direction (Fagundes et al 2016;Fricke et al 2015). This study did not take burrow orientation into account, but it is likely that 64 Manx Shearwaters also favour burrows face away from prevailing wind to reduce the effect of wind chill and rainfall.…”
Section: Effects Of Windmentioning
confidence: 94%
“…However, in extreme cases burrows can be a disadvantage, during periods of heavy precipitation burrows can become flooded and heat waves can lead to heat stress (Chambers et al 2011). Burrow flooding, and its impact on chick thermoregulation, has been documented as a cause of chick and egg mortality in many species, including penguins, shearwaters and storm-petrels (Bancroft et al 2005;Boersma and Rebstock 2014;Chambers et al 2011;Huntington et al 1996;Fagundes et al 2016;Serventy and Curry 1984).…”
Section: Burrow-nesting Speciesmentioning
confidence: 99%
See 2 more Smart Citations